PENGARUH KEEFEKTIFAN WEBSITE SEKOLAH TERHADAP CITRA SEKOLAH MENURUT ORANG TUA PESERTA DIDIK DI LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) SE-KOTA MALANG - Feni Nur Anggraeni; Maisyaroh Maisyaroh; Imam Gunawan; Feni Nur Anggraeni; Maisyaroh Maisyaroh (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine (1) the level of website effectiveness in PAUDinstitutions in Malang City; (2) description of institutional image in PAUD institutionsin Malang City; (3) the effect of the effectiveness of the school website on the imageof the school according to the parents of students in PAUD institutions throughoutMalang. This research uses a quantitative approach using aapproach descriptivecorrelational. The results of this study indicate the level of effectiveness of websitesin PAUD institutions in Malang is in the medium category, as well as the significantinfluence between the effectiveness of the website on the image of schools in PAUDinstitutions throughout Malang.